An Evolutionary Approach to Financial Innovation - Bettzuge, Marc Oliver; Hens, Thorsten (Review of Economic Studies, 2001)
The purpose of this paper is to explain why some markets for financial products take off while others vanish as soon as they have emerged. To this end, we model an infinite sequence of CAPM-economies in which financial products can be used for insurance purposes. Agents' participation in these financial products, however, is restricted. Consecutive stage economies are linked by a mapping (“transition function”) which determines the next period's participation structure from the preceding period's participation. The transition function generates a dynamic process of market participation which is driven by the percentage of informed traders and the rate at which a new asset is adopted. We then analyse the evolutionary stability of stationary equilibria. In accordance with the empirical literature on financial innovation, it is obtained that the success of a financial innovation, a mutation, depends on a sufficiently high trading volume, marketing, and new and differentiated hedging opportunities. In particular, a set of complete markets forming a stationary equilibrium is robust with respect to any further financial innovation while this is not necessarily true for a set of incomplete markets.